Paraneoplastic Pemphigus Involving the Respiratory and Gastrointestinal Mucosae - Kentaro Odani; Akane Itoh; Soshi Yanagita; Yasuhito Kaneko; Mitsuhiro Tachibana; Takashi Hashimoto; Yutaka Tsutsumi (Case Reports in Pathology)
Paraneoplastic pemphigus (PNP), an autoimmune mucocutaneous disorder involving the oral and bronchial mucosae, is a rare complication of hematologic malignancy. Serologically, serum autoantibodies against varied desmosome-related proteins are of notice. PNP is often lethal due to bronchiolitis obliterans and opportunistic infection. A 70-year-old Japanese male complained of dry cough, stomatitis, and sore throat. The lips and oral mucosa were severely eroded, and skin eruptions were seen on the chest and abdomen. The biopsy features were consistent with PNP, and the deposition of IgG and IgM was shown on the plasma membrane of the involved keratinocytes. Serological studies demonstrated autoantibodies to desmoglein-3, desmocollins-2 and -3, bullous pemphigoid antigen-1, envoplakin and periplakin. Systemic evaluation disclosed mantle cell lymphoma, stage 4B. After chemotherapy, partial remission was reached. PNP was treated with methylprednisolone and intravenous immunoglobulins, and the oral lesion only temporarily responded. He died of respiratory failure two months after onset. Autopsy revealed residual indolent lymphoma and systemic opportunistic infections. Aspergillus colonized the eroded bronchial/bronchiolar mucosa, associated with extensive vascular invasion. Coinfection of cytomegalovirus (CMV) and Pneumocystis jirovecii caused interstitial pneumonia. The oropharyngeal, respiratory, esophageal, and gastrointestinal mucosae were diffusely infected by CMV. Bronchiolitis obliterans was observed in the peripheral lung. PNP-related acantholysis-like lesions were microscopically identified in the bronchial and gastrointestinal mucosa. IgG deposition and cleaved caspase-3-immunoreactive apoptotic cell death were proven in the involved mucosal columnar cells. Pathogenesis of the mucosal involvement is discussed.